The buying motives analysis of consumer electric vehicle in Indonesia - Pamungkas, Benni Ahdiyana (Universitas Negeri Malang, 2025)
Climate change has prompted many countries to decarbonize their economies, with the development of the electric vehicle (EV) industry being one of the proposed solutions. However, EV sales in Indonesia have fallen short of expectations. Understanding consumer purchasing motives is crucial to accelerating EV adoption. Unfortunately, research on the factors driving EV purchases remains limited. This study seeks to address this gap by identifying the dominant factors influencing consumer decisions to purchase EVs in Indonesia. This research employs a quantitative approach with a survey research strategy. A non-probability sampling method using a purposive sampling technique was applied, resulting in a sample of 103 respondents. Exploratory factor analysis was conducted to analyze the data. The findings identify six key factors influencing EV purchasing decisions: Total Customer Benefits, Climate Change Awareness, Product Value, Emotional and Rational Impacts, Economic and Environmental Considerations, and Electric Vehicle Charging Stations (EVCS). Among these, Total Customer Benefits emerged as the most dominant factor.